2015
DOI: 10.1093/mnras/stv2288
|View full text |Cite
|
Sign up to set email alerts
|

H-atom addition and abstraction reactions in mixed CO, H2CO and CH3OH ices – an extended view on complex organic molecule formation

Abstract: Complex organic molecules (COMs) have been observed not only in the hot cores surrounding low-and high-mass protostars, but also in cold dark clouds. Therefore, it is interesting to understand how such species can be formed without the presence of embedded energy sources. We present new laboratory experiments on the lowtemperature solid state formation of three complex moleculesmethyl formate (HC(O)OCH 3 ), glycolaldehyde (HC(O)CH 2 OH) and ethylene glycol (H 2 C(OH)CH 2 OH)through recombination of free radica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
230
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 198 publications
(251 citation statements)
references
References 52 publications
(47 reference statements)
21
230
0
Order By: Relevance
“…More recently, Chuang et al (2016) presented new laboratory experiments on the low-temperature solid-state formation of three complex molecules, i.e., methyl formate (HC(O)OCH3), glycolaldehyde and ethylene glycol, through recombination of free radicals formed via H-atom addition and abstraction reactions that occur during the hydrogenation of CO ice at 15 K. The experiments include the co-deposition of H atoms and pure H 2 CO, H atoms and pure CH 3 OH as well as H atoms and mixtures of H 2 CO with CO, H 2 CO with CH 3 OH, and CH 3 OH with CO, in fact extending previous CO hydrogenation studies (e.g., Fuchs et al 2009;. The aim of these experiments is to resemble the physical-chemical conditions typical of the CO freeze-out stage in dark molecular clouds, when H 2 CO and CH 3 OH form by the recombination of accreting CO molecules and H atoms on ice grains.…”
Section: Test Case: Hydrogenation Of Co Ice Leading To Complex Moleculesmentioning
confidence: 99%
“…More recently, Chuang et al (2016) presented new laboratory experiments on the low-temperature solid-state formation of three complex molecules, i.e., methyl formate (HC(O)OCH3), glycolaldehyde and ethylene glycol, through recombination of free radicals formed via H-atom addition and abstraction reactions that occur during the hydrogenation of CO ice at 15 K. The experiments include the co-deposition of H atoms and pure H 2 CO, H atoms and pure CH 3 OH as well as H atoms and mixtures of H 2 CO with CO, H 2 CO with CH 3 OH, and CH 3 OH with CO, in fact extending previous CO hydrogenation studies (e.g., Fuchs et al 2009;. The aim of these experiments is to resemble the physical-chemical conditions typical of the CO freeze-out stage in dark molecular clouds, when H 2 CO and CH 3 OH form by the recombination of accreting CO molecules and H atoms on ice grains.…”
Section: Test Case: Hydrogenation Of Co Ice Leading To Complex Moleculesmentioning
confidence: 99%
“…The intensity of the regular H 2 CO isotope (m/z = 30, not shown here) is about two orders of magnitude higher, in accordance with the 12 C/ C 13 natural abundance ratio. Two other desorption peaks, at ∼160 and ∼200 K, can be respectively assigned to unprocessed glycolaldehyde, left over after co-deposition, and to HOCH 2 CH 2 OH, a known reaction product upon HOCH 2 CHO hydrogenation (Burke et al 2015;Fedoseev et al 2015;Chuang et al 2015;Maity et al 2015). The detection of the formed H CO 2 , CH 3 OH, and HOCH 2 CH 2 OHin addition to the low-volatile product desorbing at 240 K is fully consistent with the reaction scheme presented in Figure 1.…”
Section: Glycerolmentioning
confidence: 99%
“…CH 3 OH ice has been observed in dense clouds (Pontoppidan et al 2003;Bottinelli et al 2010;Boogert et al 2015), and its abundance is in line with the predictions of theoretical and modeling work (Tielens & Hagen 1982;Shalabiea & Greenberg 1994;Geppert et al 2005;Cuppen et al 2009Cuppen et al , 2011Vasyunin & Herbst 2013a). Recent experimental and theoretical studies demonstrated that twocarbon-bearing COMs, i.e., glycolaldehyde and ethylene glycol, are also formed at this stage (Woods et al 2012;Fedoseev et al 2015;Butscher et al 2015;Chuang et al 2015). The key point in the formation of these species appears to be the recombination of free intermediate radicals, i.e., HĊO or ·CH 2 OH, produced in the sequence of H-atom addition and abstraction reactions along the aforementioned CH 3 OH formation route (see Figure 8 of Chuang et al 2015 for more details).…”
Section: Proposed Reaction Schemementioning
confidence: 99%
See 2 more Smart Citations